A review of fertilizer use in Malaysian forest plantations: Future plans for sustainable forestry - Thamer A. Thabet; Normah Awang Besar @ Raffie; Affendy Hassan (Canadian Center of Science and Education, 2025)
Limited reviews to date, and subsequently we have discussed the factors that affect forest plantations’ ability to produce sustainably, such as fertilizer usage and silviculture. The creation of an appropriate framework for managing tree fertilization for planted forests in the future will be aided by previous studies and present requirements. Here, we will discuss the various approaches to ensure effective and efficient fertilizer management in the plantations, along with the challenges and future trends in fertilizer management systems for sustainable forest plantations in Sabah, Malaysia. Applying bio-fertilizers is therefore a good way to improve and preserve the soil’s nutrient economy, which lowers the need for chemical fertilizers for efficient and sustainable farming. This study presents the most recent and practical technologies for applying different fertilizers to seedlings in forests and nurseries.